Understanding energy savings in a crisis: The role of prices and non-monetary factors - Sophie M. Behr; Till Köveker; Merve Kücük (Deutsches Institut für Wirtschaftsforschung (DIW), 2025)
Russia's invasion of Ukraine in 2022 was accompanied by a significant reduction of its gas supply to Europe, causing sharp energy price surges and prompting governments to respond with public appeals and programs aimed at reducing consumption. This paper investigates the effects of price increases and non-monetary factors, such as public appeals and saving programs, on residential energy savings during the crisis. Using a unique building-level dataset on residential energy consumption and prices in Germany, we identify price-driven savings and energy price elasticities with a DiD-PSM approach. By comparing buildings that faced price increases to buildings with constant prices, we can isolate price-driven savings from contemporaneous non-monetary effects. Our findings reveal that while increased prices led to moderate short-run energy savings, the majority of observed savings were driven by non-monetary factors. Consequently, we identify a relatively low short-run price elasticity of residential heat energy demand of -0.07. Going beyond average effect estimation, we use two machine learning methods to calculate building-level price-driven and non-price-driven savings, then analyzing their variation with socio-economic characteristics using census data.
Keywords: Q41; Q48; 330; Energy crisis; Energy policy; Causal inference; Double machine learning